Teratoid Wilms Tumor: Report of Three Cases and Review of the Literature - Doaa AL GHAMDI; Nasir BAKSHI; Mohammed AKHTAR (Federation of Turkish Pathology Societies, 2019)
Teratoid Wilms tumor is a rare variant of Wilms tumor composed predominantly of well-differentiated epithelial and/or mesenchymal heterologous elements. Like the classical Wilms tumor, this variant may also occur as a renal mass or may be found in extra renal locations. This tumor may be treated effectively by surgical resection; however, it generally fails to respond to chemotherapy. A review of the literature revealed 30 reported cases of intra renal and 5 reports of extra renal teratoid Wilms tumor. We report our experience with an additional three cases of renal teratoid Wilms tumor adding to the 30 cases previously reported.